2011
DOI: 10.1074/jbc.m111.293969
|View full text |Cite
|
Sign up to set email alerts
|

MyD88 Interacts with Interferon Regulatory Factor (IRF) 3 and IRF7 in Atlantic Salmon (Salmo salar)

Abstract: Background: MyD88 directly interacts and affects IRF activation in mammals, but no information has been available about lower vertebrates. Results: Transgenic MyD88 interacts with IRF3 and IRF7A/B and modulates the IRF-induced IFN response and accumulates in aggresomes in Atlantic salmon. Conclusion: MyD88 is involved in the regulation of the IRF-induced IFN response in Atlantic salmon. Significance: The results shed light on the evolution of the innate immune response in vertebrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 69 publications
1
17
0
Order By: Relevance
“…For example, IRF4 can negatively regulate of TLR signaling by targeting MyD88 (20) and IRF8 interacts with TRAF6 to participate in the MyD88dependent activation of NF-κB to induce pro-inflammatory cytokines in mammals (42). Interestingly, previous studies have reported that fish (Atlantic salmon) MyD88 interacted with IRF3 and was involved in the positive regulation of IRF-induced IFN response (43). IRF3 can positively regulate NF-κB pathway, according to our results.…”
Section: Discussionsupporting
confidence: 82%
“…For example, IRF4 can negatively regulate of TLR signaling by targeting MyD88 (20) and IRF8 interacts with TRAF6 to participate in the MyD88dependent activation of NF-κB to induce pro-inflammatory cytokines in mammals (42). Interestingly, previous studies have reported that fish (Atlantic salmon) MyD88 interacted with IRF3 and was involved in the positive regulation of IRF-induced IFN response (43). IRF3 can positively regulate NF-κB pathway, according to our results.…”
Section: Discussionsupporting
confidence: 82%
“…A previous study in which the expression of surface MHCII was analyzed in salmon HK and spleen leukocytes identified a population of granular cells which expressed relatively high levels of surface MHCII but had a low capacity to endocytose dextran and Ova (Iliev et al, 2011; Lagos et al, 2012). In the current study, the morphology of sorted cells, examined using May Grünwald–Giemsa staining and TEM indicate that these cells are most likely polymorphonuclear granulocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The protein samples prepared in LDS buffer were analysed as previously described [35] using NuPAGE Novex Bis-Tris 4–12% gels (Life Technologies). The SsTLR9 antibody has been previously characterized [15] and was used at 1:1000-fold dilution.…”
Section: Methodsmentioning
confidence: 99%
“…To visualise endolysosomes in live cells, CHSE cells grown in Lab-Tek™ Chambered Coverglass slides (Nunc) were incubated with 1 μM LysoSensor™ Green DND-189 (Life technologies) for 30 min, washed and subjected directly or following the indicated stimulations with CpG-B-Cy5 (Eurogenetech) to confocal microscopy. The transfections of CHSE and TO cells were performed using FuGeneHD (Roche) as previously described [35], The expression constructs include pDEST12.2 (Invitrogen), pDESTEGFP C1 [35] and pDEST12.2-SsTLR9 [39]. SYTOX ® Green and 7-aminoactinomycin D (7-AAD), which were used to stain cell nuclei, were purchased from Life Technologies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation